Levofloxacin-Induced Acute Hyperpigmentation Changes in a Chronic Kidney Disease Patient - Shakuntala S. Patil; Sachin M. Patil; Ryan Campbell; Manisha Singh; Matthew Plotkin (Case Reports in Medicine)
Medication-induced cutaneous hyperpigmentation has variable clinical presentations and is dependent on the specific drug involved. Most commonly, an attentive patient observes such changes early in the course; when missed by the patient, such changes are usually noted by an observant clinician. Clinical diagnosis can be challenging if the patient is on multiple medications because other causes must be excluded. This condition occurs via multiple mechanisms. Frequently, the pigmentary change is reversible with discontinuation of the drug. Causative medications include nonsteroidal; anti-inflammatory agents, antimalarials, antibiotics, psychotropics, amiodarone, and chemotherapeutic agents. The; antimicrobials responsible for hyperpigmentation are antimalarials, tetracyclines, tigecycline, dapsone, rifampicin, and antiretrovirals such as zidovudine. Sunlight exposure can worsen the pigmentation seen with some of the above antimicrobials (e.g., dapsone). Here, we describe an older adult white woman presenting with acute cutaneous; hyperpigmentation of the bilateral lower extremities while on levofloxacin therapy. Hyperpigmentation resolved after cessation of the agent. Our case highlights this unique acute presentation after only a few days of oral levofloxacin.